Innovative Role of Blockchain Pharmaceutical Supply Chain Digital Transformation: Enterprise Architecture Perspective - Wedha, Bayu Yasa; Vasandani, Michael Sagar; Wedha, Alessandro Enriqco Putra Bayu (Politeknik Ganesha Medan, 2023)
The advent of the Fourth Industrial Revolution has compelled numerous industries to undergo digital changes or transformations. One example is the pharmaceutical industry, which is responsible for providing medicinal products. The pharmaceutical supply chain assumes a crucial position within the pharmaceutical industry as it enables the secure, streamlined, and dependable transportation of medications from producers to individuals in need. The issue of prioritizing digital transformation within the pharmaceutical supply chain has emerged as a significant problem for hospitals and pharmaceutical businesses. Integrating different components inside the system is effectively supported by the substantial function fulfilled by Enterprise Architecture in this specific context. The objective is to minimize errors, enhance inventory management, optimize product distribution, and guarantee the safety and quality of pharmaceuticals. However, the process of adequately monitoring and verifying data has its challenges. However, these challenges can be efficiently addressed through implementing blockchain technology. In addition to this, Blockchain technology has the potential to enhance industrial efficiency. Utilizing blockchain technology enables the facilitation of transparency, immutability, and data integrity across the entirety of the supply chain. Integrating Enterprise Architecture electronic automation with Blockchain technology enables pharmaceutical enterprises to establish robust systems facilitated by Smart Contracts. The use of this system is expected to significantly enhance automation and regulatory adherence within supply chain processes, leading to notable advancements in operational efficiency, security, and data accuracy. Integrating blockchain technology and smart contracts enables pharmaceutical enterprises to enhance their product offers to hospitals and patients at reduced expenses, facilitating notable advancements in Enterprise Architecture.